Superinfection by discordant subtypes of HIV-1 does not enhance the neutralizing antibody response against autologous virus. - Luzia M Mayr; Rebecca L Powell; Johnson N Ngai; William A Takang; Arthur Nádas; Phillipe N Nyambi (PLoS ONE, 2012)
Recent studies have demonstrated that both the potency and breadth of the humoral anti-HIV-1 immune response in generating neutralizing antibodies (nAbs) against heterologous viruses are significantly enhanced after superinfection by discordant HIV-1 subtypes, suggesting that repeated exposure of the immune system to highly diverse HIV-1 antigens can significantly improve anti-HIV-1 immunity. Thus, we investigated whether sequential plasma from these subjects superinfected with discordant HIV-1 subtypes, who exhibit broad nAbs against heterologous viruses, also neutralize their discordant early autologous viruses with increasing potency. Comparing the neutralization capacities of sequential plasma obtained before and after superinfection of 4 subjects to those of matched plasma obtained from 4 singly infected control subjects, no difference in the increase in neutralization capacity was observed between the two groups (p = 0.328). Overall, a higher increase in neutralization over time was detected in the singly infected patients (mean change in IC(50) titer from first to last plasma sample: 183.4) compared to the superinfected study subjects (mean change in IC(50) titer from first to last plasma sample: 66.5). Analysis of the Breadth-Potency Scores confirmed that there was no significant difference in the increase in superinfected and singly infected study subjects (p = 0.234). These studies suggest that while superinfection by discordant subtypes induces antibodies with enhanced neutralizing breadth and potency against heterologous viruses, the potency to neutralize their autologous viruses is not better than those seen in singly infected patients.